1996
DOI: 10.1128/aem.62.4.1214-1219.1996
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of pentaerythritol tetranitrate by Enterobacter cloacae PB2

Abstract: A mixed microbial culture capable of metabolizing the explosive pentaerythritol tetranitrate (PETN) was obtained from soil enrichments under aerobic and nitrogen-limiting conditions. A strain of Enterobacter cloacae, designated PB2, was isolated from this culture and was found to use PETN as a sole source of nitrogen for growth. Growth yields suggested that 2 to 3 mol of nitrogen was utilized per mol of PETN. The metabolites pentaerythritol dinitrate, 3-hydroxy-2,2-bis-[(nitrooxy)methyl]propanal, and 2,2-bis-[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
10

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 18 publications
5
54
0
10
Order By: Relevance
“…Dadook et al (2014) observed that optimal growth of various strains of Azotobacter chroococcum occurred at 6 ppm to 20 ppm ZnSO 4 , and suggested that higher concentrations of Zn in agricultural soil are harmful to beneficial microorganisms and reduce soil fertility. Several species of Enterobacter have been identified, and their ability to degrade phosphonate, glyphosate, pentaerythritol tetranitrate, trinitrotoluene, organophosphates, lignin and synthetic dyes has been reported (Lee et al 1992;Dick & Quinn 1995;Binks et al 1996;French et al 1998;Singh et al 2004;Manter et al 2011;Mukherjee & Das 2014). The efficiency of using Enterobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Dadook et al (2014) observed that optimal growth of various strains of Azotobacter chroococcum occurred at 6 ppm to 20 ppm ZnSO 4 , and suggested that higher concentrations of Zn in agricultural soil are harmful to beneficial microorganisms and reduce soil fertility. Several species of Enterobacter have been identified, and their ability to degrade phosphonate, glyphosate, pentaerythritol tetranitrate, trinitrotoluene, organophosphates, lignin and synthetic dyes has been reported (Lee et al 1992;Dick & Quinn 1995;Binks et al 1996;French et al 1998;Singh et al 2004;Manter et al 2011;Mukherjee & Das 2014). The efficiency of using Enterobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…1). No growth of isolate VH1 was observed above that of a negative control lacking amino acids when it was screened for its ability to utilise a range of aminophosphonates (2AEP, 3-aminopro- Results were scored negative if the protein yield, as measured by the method of Binks et al [12], was less than 20% of that of the positive control containing 1 mM inorganic phosphate. Results are means of duplicates which on no occasion varied by more than 5%.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphate release during growth was assayed for by the method of Fiske and SubbaRow [11]. Maximal growth was expressed as the yield of protein ml 31 from cultures as determined by the method of Binks et al [12].…”
Section: Screening For Organophosphonate Utilisationmentioning
confidence: 99%
“…Inorganic phosphate was determined by the colorimetric method of Fiske and SubbaRow [11]. The protein yield from K. fragilis cultures was assayed by the method of Binks et al [12] ; protein concentration in cell extracts was measured by the method of Bradford [13].…”
Section: Methodsmentioning
confidence: 99%